Small Eden in Los Angeles: Garrett Eckbo's garden (1950-1965) - Tuset Davó, Juan José (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
For 15 years, the American landscape architect Garrett Eckbo designed and lived in the garden of his modern house in the hills of Los Angeles. The experience in the thoughtful and time-consuming construction of his outdoor room reflects not only the arguments that interested him and help to stimulate the imagery of the Californian domestic garden but also his considerations about the form of the space of this room: the existence of constructions that extended life outside, the exploration of the possibilities of modern art in the garden or the presence of the water in the swimming pool. This garden, and the house, testifies the domesticity of an artificial nature that pursues the renewal of the idea of intimacy in the face of inherited history. The article describes this project and thinks of it from its leaved contribution as a continuous outdoor space construction made of living and inert matter that improves the house. This reflection frames in a speculations on the city of Los Angeles in order to suggest that Eckbo's small Edenic garden, in terms of its particular radical production of a private nature, could be the ember of a latent ecology that helps us in the humanization of the modern city.
Keywords: Eckbo; Wonderland Park; aluminium; ALCOA; self-experimentation